DYNAMICS OF CARBON EMISSIONS IN ASEAN: PANEL ARDL APPROACH - Nugraha, Galih; Dodi Tirtana; Muhammad Nurhikmat; Dim Zarita Suryanugraha (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2025)
This study analyzes the short- and long-run relationship between economic growth, population, manufacturing, foreign direct investment (FDI), and deforestation on carbon emissions in ASEAN countries, one of the fastest-growing economic regions. Using annual panel data from 1991–2023 for nine countries, this study adopts the Panel Autoregressive Distributed Lag (ARDL) and Error Correction Model (ECM) approaches. Diagnostic tests, including the Im Pesaran, & Shin (IPS) unit root test, confirmed the model's validity with variables having mixed orders of stationarity. The ECM estimation results show a significant long-run cointegration relationship. In the long run, GDP per capita, population, and the manufacturing sector have a positive and significant effect on carbon emissions. In contrast, FDI has a negative and significant impact. Furthermore, the Panel Granger causality test showed that no independent variable can significantly predict changes in carbon emissions. Overall, these findings provide an empirical basis for policies that balance economic and environmental aspirations. The main implication is the importance of formulating a strategy to decouple growth from emissions through an efficient industrial transition and by attracting sustainable investment.